2023
DOI: 10.3390/genes14051050
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals the Age-Related Developmental Dynamics Pattern of the Longissimus Dorsi Muscle in Ningxiang Pigs

Abstract: The growth and development of the Longissimus Dorsi muscle are complex, playing an important role in the determination of pork quality. The study of the Longissimus Dorsi muscle at the mRNA level is particularly crucial for finding molecular approaches to improving meat quality in pig breeding. The current study utilized transcriptome technology to explore the regulatory mechanisms of muscle growth and intramuscular fat (IMF) deposition in the Longissimus Dorsi muscle at three core developmental stages (natal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…In the study, 51 DEGs associated with muscle development were identified during the growth and development stages of mink. Notably, IGF2, MYOG, MEGF10, MYMX, MYMK, SOX8, and PITX1 exhibited upregulated expression at 45 days, with stronger expression in skeletal muscle satellite cells where they play crucial roles in muscle regeneration [7,27,28]. Furthermore, it has been observed that certain genes exhibit a requirement for cooperative interactions in order to ensure their proper functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study, 51 DEGs associated with muscle development were identified during the growth and development stages of mink. Notably, IGF2, MYOG, MEGF10, MYMX, MYMK, SOX8, and PITX1 exhibited upregulated expression at 45 days, with stronger expression in skeletal muscle satellite cells where they play crucial roles in muscle regeneration [7,27,28]. Furthermore, it has been observed that certain genes exhibit a requirement for cooperative interactions in order to ensure their proper functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studying the genetic regulatory mechanisms of mink growth is crucial for the mink breeding industry. In recent years, with the rapid development of sequencing technology, genomics has been widely used in the study of molecular regulation mechanisms of animal growth and development, promoting the process of animal genome selection breeding [3][4][5][6][7]. However, the relevant research on mink is still lagging behind.…”
Section: Introductionmentioning
confidence: 99%
“…PPARGC1A plays a crucial role in reducing lipid deposition [ 53 ]. UBC , SLC27A5 , RXRG , PRKCQ , PRKAG2 , PPARGC1A , PLIN5 , PLIN4 , IRS2 , and CPT1B play a role in regulating the growth and development of the longissimus dorsi muscle in Ningxiang pigs [ 54 ]. The genes PPARA , PPARG , SREBF1 , and PPARGC1A genes are involved in regulating fat deposition in the longissimus dorsi muscle of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we detected candidate genes related to meat quality traits in Tunchang pigs. The GYS1 gene is involved in skeletal muscle glycogen synthesis [60], the PHLPP1 gene may be involved in bone development [61], and the SLC27A5 gene may play a key role in intramuscular fat deposition [62]. Additionally, the CRTC1 gene, which was enriched in our Tunchang pig population, has been reported to regulate fat deposition and indirectly affect meat quality traits [63].…”
Section: Candidate Genes Identified On Roh Islandsmentioning
confidence: 91%